Praktik Perjudian dalam Pilkada: Studi Kasus pada Pilkada Kabupaten Sumba Barat Tahun 2024 di Kecamatan Wanukaka - Artha Juwian Djolla Kahowi; Esrah D. N. A. Benu; Philips Y.N Ndoda (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
This study aims to examine gambling practices in the 2024 Regional Head Election (Pilkada) of West Sumba Regency, particularly in Wanukaka District. The research employs a qualitative approach with a case study method to understand the forms of gambling practices, the motives behind them, and the meanings attached by the community to this phenomenon within the context of local politics. Data were collected through in-depth interviews, observations, and documentation involving purposively selected informants. Data analysis was conducted using a descriptive qualitative method with a phenomenological approach to gain a deeper understanding of community experiences and perceptions. The findings reveal that gambling practices during the Pilkada are not solely driven by economic motives or the expectation of financial gain but are also influenced by political and social factors. Gambling is perceived as a means of predicting election outcomes, interpreting political dynamics, strengthening group solidarity, and expressing support for particular candidates. This phenomenon has evolved into a social habit considered acceptable by some members of the community despite being contrary to existing legal provisions. The existence of gambling practices in local elections affects political behavior, has the potential to influence voters’ political choices, and contributes to challenges affecting the quality of local democracy and the integrity of the electoral process.